Pemodelan Aplikasi Pendeteksi Pelaksanaan Social Distancing dalam Membantu Pengawasan Program 3M - Arnold Nasir; Stefany Yunita Baralangi (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2022)
The Coronavirus has made severe damage to the society around the world. Every aspect of human life was affected. As the result, the government propose the “new normal” policy to be applied as the new standards for regulating people in doing their activities. One of the rules within the new normal policy is to implement social distancing in a public space. In order to enforce the rule, the implementation of computer vision technology by using CNN becomes one of the solutions, especially in the university environment.